PENGARUH PENGALAMAN, BUDGET DAN MASA KONTRAK AUDIT TERHADAP KUALITAS AUDIT EKSTERNAL (Studi Kasus Kantor Akuntan Publik Kota Malang) - Alifiah Salsabilah; Nur Diana; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to examine the effect of experience, budget and audit contract period on external audit quality. The variables used in this study are the external audit quality variable as the dependent variable, while the independent variables are experience, budget and audit contract period. Research data obtained from questionnaires with the number of samples used as respondents as many as 31 respondents. The results of this study simultaneously concluded that there was an influence between the variables of experience, budget and audit contract period on external audit quality and partially concluded that the experience variable had a positive and significant impact on audit quality, audit budgets had a significant negative effect on audit quality, while the audit contract period did not. effect on audit quality. Keywords: Audit quality, budget, audit experience, audit contract period